Crisis and cultural change: the countries with adjustment programmes in the European Union - Casanova, J. L. (Comparative Sociology, 2018)
After the financial crisis in 2008 significant changes occurred in the European Union, particularly in the countries that had adjustment programmes. According to empirical work by Hofstede, Inglehart and Schwartz it’s predictable that societal changes have a cultural impact. Data from European Social Survey since 2002 show that changes in political orientations are bigger than in Human Values, and deepen after 2008. Changes in countries that had adjustment programmes diverge significantly from those in the rest of the Eurozone, mainly on political orientations. Bigger challenges to the EU come from the extensive fall on trust in politics, the European Parliament and satisfaction with democracy, the rise of the values of Tradition and Security, and the decrease of Self-direction. This evolving cultural conservatism associated with continued degradation of democracy is nurturing nationalism and authoritarianism.